Theoretical and practical issues of researching the characteristics of the formation of social tolerance in students - Rano Karimovna Boykuziyeva (Zien Journals, 2023)
This article provides information about the concept of tolerance and empathy, the ideas of tolerance, the development of a sense of tolerance, modern approaches to empathy, and the concept of the differentiation of the phenomenon of tolerance.
Keywords: tolerance; empathy; differentiation; idea